Complex formation with monomeric α-tubulin and importin 13 fosters c-jun protein stability and is required for c-jun’s nuclear translocation and activity - Kappelmann-Fenzl, Melanie; Kuphal, Silke; Krupar, Rosemarie; Schadendorf, Dirk; Umansky, Viktor; Vardimon, Lily; Hellerbrand, Claus; Boßerhoff, Anja Katrin (Cancers, 2019)
Microtubules are highly dynamic structures, which consist of α-and β-tubulin heterodimers. They are essential for a number of cellular processes, including intracellular trafficking and mitosis. Tubulin-binding chemotherapeutics are used to treat different types of tumors, including malignant melanoma. The transcription factor c-Jun is a central driver of melanoma development and progression. Here, we identify the microtubule network as a main regulator of c-Jun activity. Monomeric α-tubulin fosters c-Jun protein stability by protein–protein interaction. In addition, this complex formation is necessary for c-Jun’s nuclear localization sequence binding to importin 13, and consequent nuclear import and activity of c-Jun. A reduction in monomeric α-tubulin levels by treatment with the chemotherapeutic paclitaxel resulted in a decline in the nuclear accumulation of c-Jun in melanoma cells in an experimental murine model and in patients’ tissues. These findings add important knowledge to the mechanism of the action of microtubule-targeting drugs and indicate the newly discovered regulation of c-Jun by the microtubule cytoskeleton as a novel therapeutic target for melanoma and potentially also other types of cancer.
CRIS-Team Scopus Importer:2019-11-29
Keywords: AP1; C-Jun; Importin; Transcription factor; Tubulin